Sequential Vector Packing - Cieliebak, Mark; Hall, Alexander; Jacob, Riko; Nunkesser, Marc (Combinatorics, Algorithms, Probabilistic and Experimental Methodologies, 2007)
We introduce a novel variant of the well known d-dimensional bin (or vector) packing problem. Given a sequence of non-negative d-dimensional vectors, the goal is to pack these into as few bins as possible of smallest possible size. In the classical problem the bin size vector is given and the sequence can be partitioned arbitrarily. We study a variation where the vectors have to be packed in the order in which they arrive and the bin size vector can be chosen once in the beginning. This setting gives rise to two combinatorial problems: One in which we want to minimize the number of used bins for a given total bin size and one in which we want to minimize the total bin size for a given number of bins. We prove that both problems are ${\mathcal{NP}}$ -hard and propose an LP based bicriteria $(\frac1ε, \frac1{1-ε})$ -approximation algorithm. We give a 2-approximation algorithm for the version with bounded number of bins. Furthermore, we investigate properties of natural greedy algorithms, and present an easy to implement heuristic, which is fast and performs well in practice.